Assessment of Awareness, Attitudes and Perceptions of Students on HIV Vaccine Trials at the University of Dar es salaam, Tanzania (Tanzania Medical Journal, 2009)
Objective: To assess the awareness, attitude and perceptions on HIV AND AIDS vaccine trials among students at the University of Dar es Salaam, TanzaniaStudy design: This was a descriptive cross sectional study Setting: University of Dar es Salaam, Tanzania Results: A total of 384 were recruited in the study. Out of these41.7% reported that HIV vaccine can not prevent the spread of HIV. One hundred and four (26.8%) were of the opinion that an HIV vaccine can cause infection to the person vaccinated. A total of 317 (82.0%) perceived an HIV vaccine as an addition rather than asubstitute to other existing preventive measures such as condom use, in the fight against HIV and AIDS. The attitude towards an HIV vaccine trial was positive in 87.5% of the students, but only 19.8% would be willing to participate in a vaccine trial with their currentlevel of information. However, 48.2% would participate if they are better informed.Conclusion: The perception and attitude of University of Dar es Salaam students towards HIV vaccine trials were generally positive. However misconceptions were common.Recommendations: The community should be educated more on HIV vaccine trials, and more socio-behavioral studies need to be done among different social groups on HIV vaccine trials. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 5-8